INVESTMENT BEHAVIOUR OF INVESTORS IN MUTUAL FUNDS & ULIPS- A CASE STUDY OF HARYANA REGION - Gulia, Suman (International Journal of Psychosocial Rehabilitation, 2020)
In today’s competitive environment, different kinds of investment avenues are available to the investors. All investment modes have advantages & disadvantages. An investor tries to balance these benefits and shortcomings of different investment modes before investing in them. Among various investment modes, Mutual Fund is the most suitable investment mode for the common man, as it offers an opportunity to invest in a diversified and professionally managed portfolio at a relatively low cost. In this paper, an attempt is made to study mainly the investment avenue i.e. mutual funds and ULIPS preferred by the investors of Haryana Region, and we have tried to analyze the investor’s preference towards investment in mutual funds when other investment avenue (ULIPS) is also available in the market.